162TiP A phase I study evaluating BI 765063, a first in class selective myeloid SIRPa inhibitor, as standalone and in combination with BI 754091, a programmed death-1 (PD-1) inhibitor, in patients with advanced solid tumours. (15th December 2019) - Marabelle, A; Cassier, P; Delord, J-P; Jungles, C; Champiat, S; Vinceneux, A; Korakis, I; Huhn, R; Poirier, N; Vasseur, B; Kotecki, N
Abstract: Background: Signal Regulatory Protein α [SIRPα] is a polymorphic protein, strongly expressed on myeloid suppressive cells. BI 765063 (OSE172), a humanized IgG4 monoclonal antibody (mAb), is a selective antagonist of SIRPα/CD47 interaction and does not bind to SIRPɣ, known to assist T cell co-stimulation and migration. BI 765063 strongly binds V1 allele, one of the 2 major functional allele of SIRPα expressed in more than 80% of general population and Asian (in 60%). Anti-tumor effect was shown in various in vivo cancer models using the validated anti-mouse SIRPα mAbs surrogate as single agent. The effect was more pronounced in combination with T checkpoint inhibitors (Gauttier V et al, 2018). BI 765063 mechanism of action includes promotion of tumor-antigen-presentation while preserving T-cell activation and increasing tumor phagocytosis. Trial Design: This study comprises a dose escalation (step 1) to determine the Dose-Limiting Toxicities, Maximum Tolerated Dose (MTD), and Recommended phase II Dose (RP2Ds) of BI 765063 monotherapy and with BI 754091, and dose-confirmation expansion cohorts (step 2). In Step 1, ascending doses of BI 763063 every 3 weeks intravenously (iv) using a Bayesian approach with overdose control are tested. When MTD determined, BI 763063 will be tested with BI 754091, a PD-1 mAb inhibitor. In step 2, 2 parallel randomized, non-comparative mono and combination cohorts will further confirm the RP2Ds and assess the safety and preliminary efficacy (RECIST 1.1 and iRECIST). Patients ≥ 18 years, PS:0-1, with advanced solid tumor who failed or are not eligible to standard therapy will be included. V1/V1 and V1/V2 patients (central testing) are evaluated in separate cohorts in step 1. In step 2 selected population of V1/V1 patients with selected advanced-stage cancers will be included. Pharmacokinetics (PK), SIRPα receptor occupancy (RO) and a comprehensive translational program (in blood and tumour) will assess PK/PD profile and biomarkers of activity. The trial is currently active and will include 116 patients (56 in step 1 and 60 in step 2). Clinical trial identification: EudraCT: 2018-003830-34; Release date 1 October 2018. Legal entity responsible for the study: OSE Immunotherapeutics. Funding: OSE Immunotherapeutics in collaboration with Boehringer Ingelheim. Disclosure: A. Marabelle: Advisory / Consultancy: Roche, Pierre Fabre, Onxeo, EISAI, Bayer, Genticel, Rigontec, Daiichii Sankyo, Imaxio, Sanofi, BioNTech, Corvus, GLG, Deerfield, Guidepoint Global, Edimark, System Analytics, imCheck, Sotio, Bioncotech, Molecular Partners, Pillar Partners, Boehringer Inge; Advisory / Consultancy: Innate Pharma, Merck Serono, eTheRNA, Lytix pharma, Kyowa Kirin Pharma, Bayer, Novartis, Bristol-Myers Squibb, Symphogen, Genmab, Amgen, Biothera, Nektar, GSK, Oncovir, Pfizer, Seattle Genetics, Flexus Bio, Roche/Genentech, OSE immunotherapeutics, Transgene, Gritstone, M; Research grant / Funding (institution): AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, Janssen Cilag, Merck, Novartis, Pfizer, Roche, Sanofi ; Travel / Accommodation / Expenses: AstraZeneca, Bristol-Myers Squibb, Merck (MSD), Roche; Speaker Bureau / Expert testimony: Roche/Genentech, Bristol-Myers Squibb, Merck (MSD), Merck Serono, AstraZeneca/Medimmune, Amgen, Sanofi. P. Cassier: Honoraria (self): Novartis, Roche/Genentech, Blueprint Medicines, Amgen; Honoraria (institution): Novartis, Roche/Genentech, Lilly, Blueprint Medicines, Bayer, AstraZeneca, Celgene, Plexxikon, AbbVie, Bristol-Myers Squibb, Merck Serono, Merck Sharp & Dohme, Taiho Pharmaceutical, Toray Industries, Transgene, Loxo, GlaxoSmithKline, Innate Pharma, Janssen ; Travel / Accommodation / Expenses: Roche, Amgen, Novartis, Bristol-Myers Squibb, Merck Sharp & Dohme. S. Champiat: Honoraria (self): Amgen, Bristol-Myers Squibb, AstraZeneca, Janssen, MSD, Novartis and Roche; Research grant / Funding (institution): AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, Janssen Cilag, Merck, Novartis, Pfizer, Roche and Sanofi; Non-remunerated activity/ies: AstraZeneca, Bayer, Bristol-Myers Squibb, Boehringer Ingelheim, Johnson & Johnson, Lilly, Medimmune, Merck, NH TherAGuiX, Pfizer, Roche. A. Vinceneux: Advisory / Consultancy: UBS. R. Huhn: Full / Part-time employment: Boehringer-Ingelheim. N. Poirier: Shareholder / Stockholder / Stock options: Ose Immunotherapeutics; Full / Part-time employment: Ose Immunotherapeutics. B. Vasseur: Full / Part-time employment: Ose Immunotherapeutics. All other authors have declared no conflicts of interest.